Evaluation of Smoke Free Area Policy in Enrekang Regency - Nawir Rahman; Risma Niswaty; Afridha Noor Pewara (Indonesian Association for Public Administration (IAPA), 2021)
Public policy evaluation is a process of activities that are planned to assess the overall effectiveness of the program and it is deemed necessary to make changes to policies that have been carried out in order to achieve objectives. The objectives of this study are (i) How is the performance of the smoke-free area policy in Bone-bone village, Baraka sub-district, Enrekang district? (ii) What is the determinant factor in implementing the smoke-free area policy in Bone-bone village, Baraka sub-district, Enrekang district? This type of research is a descriptive study with a qualitative research design. Data collection techniques are carried out through observation, interviews and documentation. The data analysis technique used consists of data condensation, data presentation and drawing conclusions.The results of this study indicate that (i) the performance of the smoke-free area policy in Bone-bone village, Baraka sub- district, Enrekang district is quite effective, judged by the policy evaluation indicators by William N Dunn including effectiveness, efficiency, adequacy, leveling, responsiveness, and leveling. (ii) the determinant factors of the application of smoke-free areas, namely the existence of a leader or agent, a religious community, and the existence of sanctions.